Tourist Industry Development Prospects in Vladivostok under the Launch of “Primorye” Integrated Entertainment Zone - MARTYSHENKO, Natalya (Journal of Environmental Management and Tourism, 2018)
For recent years in Primorye (Russia) there has been a significant increase in the flow of inbound tourism. One of perspective trends in the tourism development is the direction related to development of the gambling zone in its territory. This article deals with the problem of the gambling business development as one of four gambling zones wherein this activity is permitted in territory of Russia - the integrated entertainment zone “Primorye”. It considers potential prospects and threats to create the gambling zone in Primorye, with evaluation of possible competitors and consumers for the newly created tourist product. With extension of benefits to conduct the business and due to adoption of the Federal law “On the free port Vladivostok” there are new opportunities to realize major projects of Primorye tourist complex. The work indicates the need to link the gambling business activity with the tourist complex in the region for the effect of synergy and development of the regional tourist infrastructure. Specific tourist objects are considered that can be used jointly with the gambling zone objects.